Superhydrophobic surfaces of the water bug Notonecta glauca: a model for friction reduction and air retention - Ditsche-Kuru, Petra; Schneider, Erik S.; Melskotte, Jan-Erik; Brede, Martin; Leder, Alfred; Barthlott, Wilhelm (Beilstein Journal of Nanotechnology, 2011)
Superhydrophobic surfaces of plants and animals are of great interest for biomimetic applications. Whereas the self-cleaning properties of superhydrophobic surfaces have been extensively investigated, their ability to retain an air film while submerged under water has not, in the past, received much attention. Nevertheless, air retaining surfaces are of great economic and ecological interest because an air film can reduce friction of solid bodies sliding through the water. This opens perspectives for biomimetic applications such as low friction fluid transport or friction reduction on ship hulls. For such applications the durability of the air film is most important. While the air film on most superhydrophobic surfaces usually lasts no longer than a few days, a few semi-aquatic plants and insects are able to hold an air film over a longer time period. Currently, we found high air film persistence under hydrostatic conditions for the elytra of the backswimmer Notonecta glauca which we therefore have chosen for further investigations. In this study, we compare the micro- and nanostructure of selected body parts (sternites, upper side of elytra, underside of elytra) in reference to their air retaining properties. Our investigations demonstrate outstanding air film persistence of the upper side of the elytra of Notonecta glauca under hydrostatic and hydrodynamic conditions. This hierarchically structured surface was able to hold a complete air film under hydrostatic conditions for longer than 130 days while on other body parts with simple structures the air film showed gaps (underside of elytra) or even vanished completely after a few days (sternites). Moreover, the upper side of the elytra was able to keep an air film up to flow velocities of 5 m/s. Obviously the complex surface structure with tiny dense microtrichia and two types of larger specially shaped setae is relevant for this outstanding ability. Besides high air film persistence, the observation of a considerable fluid velocity directly at the air–water interface indicates the ability to reduce friction significantly. The combination of these two abilities makes these hierarchically structured surfaces extremely interesting as a biomimetic model for low friction fluid transport or drag reduction on ship hulls.
Keywords: air film; aquatic insects; backswimmer; drag reduction; superhydrophobic surfaces

(untitled) - Wagner, T.; Neinhuis, C.; Barthlott, W. (Acta Zoologica (Stockholm), 1996)

(untitled) - Neinhuis, C.; Barthlott, W. (Ann. Bot. (Oxford, U. K.), 1997)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Callies, M.; Quéré, D. (Soft Matter, 2005)

(untitled) - Koch, K.; Bhushan, B.; Barthlott, W. (Soft Matter, 2008)

(untitled) - Roach, P.; Shirtcliffe, N. J.; Newton, M. I. (Soft Matter, 2008)

European Patent EP - Barthlott, W. (Self-cleaning surfaces of objects and process for producing same, 1998)

(untitled) - McHale, G.; Shirtcliffe, N. J.; Evans, C. R.; Newton, M. I. (Appl. Phys. Lett., 2009)

(untitled) - McHale, G.; Newton, M. I.; Shirtcliffe, N. J. (Soft Matter, 2010)

(untitled) - Corbett, J. J.; Koehler, H. W. (J. Geophys. Res., 2003)

(untitled) - Eyring, V.; Köhler, H. W.; van Aardenne, J.; Lauer, A. (J. Geophys. Res., 2005)

(untitled) - Barthlott, W.; Schimmel, T.; Wiersch, S.; Koch, K.; Brede, M.; Barczewski, M.; Walheim, S.; Weis, A.; Kaltenmaier, A.; Leder, A.; Bohn, H. F. (Adv. Mater., 2010)

(untitled) - Balasubramanian, A. K.; Miller, A. C.; Rediniotis, O. K. (AIAA J., 2004)

(untitled) - Jung, Y. C.; Bhushan, B. (J. Phys.: Condens. Matter, 2010)

(untitled) - Lee, C.; Kim, C. J. (Langmuir, 2009)

(untitled) - Ege, R. Z. (Allg. Physiol., 1915)

(untitled) - Thorpe, W. H.; Crisp, D. J. J. (Exp. Biol., 1947)

(untitled) - Thorpe, W. H. (Biol. Rev. Cambridge Philos. Soc., 1950)

(untitled) - Heckman, C. W. (Int. Rev. Gesamten Hydrobiol., 1983)

The insects: structure and function - Chapman, R. F. (Cambridge University Press, 1998)

An introduction to the aquatic insects of North America - Merritt, R. W.; Cummins, K. W. (Kendall Hunt, 1996)

(untitled) - Perez Goodwyn, P.; De Souza, E.; Fujisaki, K.; Gorb, S. (Acta Biomater., 2008)

Functional Surfaces in Biology: little structures with big effects - Perez Goodwyn, P. (Anti-wetting surfaces in Heteroptera (insecta): hairy solutions to any problem, 2009)

(untitled) - Balmert, A.; Bohn, H. F.; Ditsche-Kuru, P.; Barthlott, W. (J. Morphol.)

Functional Surfaces in Biology: little structures with big effects - Cerman, Z.; Striffler, B. F.; Barthlott, W. (Dry in the water: the superhydrophobic water fern Salvinia - a model for biomimetic surfaces, 2009)

Biological Atlas of Aquatic Insects - Wichard, W.; Arens, W.; Eisenbeis, G. (Apollo Books, 2002)

(untitled) - Richards, A. G.; Richards, P. A. (Int. J. Insect Morphol. Embryol., 1979)

(untitled) - Gorb, S. N. J. (Morphol., 1997)

(untitled) - Cassie, A. B. D.; Baxter, S. (Trans. Faraday Soc., 1944)

Contact Angle, Wettability, and Adhesion - Johnson, R. E., Jr.; Dettre, R. H. (Contact Angle Hysteresis. Study of an Idealized Rough Surface, 1964)

(untitled) - Herminghaus, S. (EPL, 2000)

(untitled) - Marmur, A. (Langmuir, 2006)

(untitled) - Crisp, D. J. (Trans. Faraday Soc., 1949)

(untitled) - Blow, M. L.; Yeomans, J. M. (Langmuir, 2010)

Bionik: Patente aus der Natur, Tagungsbeiträge des 5. Bionik-Kongresses der Hochschule Bremen - Ditsche-Kuru, P.; Mayser, M.; Schneider, E.; Bohn, H.; Koch, K.; Melskotte, J.-E.; Brede, M.; Leder, A.; Barczewski, M.; Weiß, A.; Kaltenmeier, A.; Walheim, S.; et al. (Eine Lufthülle für Schiffe – Können Schwimmfarn und Rückenschwimmer helfen Sprit zu sparen?, 2010)

(untitled) - Ditsche-Kuru, P.; Koop, J. H. E. (Aquatic Insects, 2009)

(untitled) - Adrian, R. J. (Annu. Rev. Fluid Mech., 1991)

Fundamentals and Applications of Microfluidics - Nguyen, N.-T.; Wereley, S. T. (Artec House, 2002)